(untitled) (E Global Congress, 2025)
Medicinal plants have been known to humankind since ancient times. Plants have long been widely used as a source of biologically active substances. The forests of Uzbekistan are distinguished by their abundance of diverse medicinal trees, shrubs, and herbaceous species. Plants nourish, clothe, and heal humans, serving as an important source of pharmaceutical and technical raw materials. For many centuries, medicinal plants remained the only source of therapeutic remedies. Since the Middle Ages, numerous scientific works describing healing plants and their use in improving human health have been passed down to us.